Successful pregnancy following transfer of embryo with dissolved zona pellucida - Hong-Xing Li (Reproductive and Developmental Medicine, 2020)
This study aimed to describe a case of a patient with the spontaneous dissolution of zona pellucida (ZP) during cleavage embryo development after intracytoplasmic sperm injection (ICSI). This patient experienced early abortion due to fetal chromosome 8 abnormality and received ICSI at 31 years of age. Time-lapse monitoring of embryo cleavage and blastocyst culture was performed, and we found that the ZP of embryos 1, 2, 4, and 5 dissolved gradually during the cleavage stage of embryo development. Five blastocysts that developed from 2 pronuclear zygotes were analyzed using next-generation sequencing, and one frozen-thawed blastocyst was transferred, resulting in intrauterine pregnancy. The results of amniotic fluid puncture showed normal fetal chromosomes. To our knowledge, this is the first report of ZP dissolution during the cleavage-stage embryo; however, the exact mechanism remains unknown. The morphological changes inferred that the granular matter in the periocular space was related to the dissolution of ZP through time-lapse observation.